Evaluation of response to stereotactic radiosurgery in patients with radioresistant brain metastases - Sayan, Mutlay; Mustafayev, Teuta Zoto; Sahin, Bilgehan; Kefelioglu, Erva Seyma Sare; Wang, Shang-Jui; Kurup, Varsha; Balmuk, Aykut; Gungor, Gorkem; Ohri, Nisha; Weiner, Joseph; Ozyar, Enis; Atalar, Banu (KOREAN SOC THERAPEUTIC RADIOLOGY \& ONCOLOGY, 2019)
Purpose: Renal cell carcinoma (RCC) and melanoma have been considered `radioresistant' due to the fact that they do not respond to conventionally fractionated radiation therapy. Stereotactic radiosurgery (SRS) provides high-dose radiation to a defined target volume and a limited number of studies have suggested the potential effectiveness of SRS in radioresistant histologies. We sought to determine the effectiveness of SRS for the treatment of patients with radioresistant brain metastases. Materials and Methods: We performed a retrospective review of our institutional database to identify patients with RCC or melanoma brain metastases treated with SRS. Treatment response were determined in accordance with the Response Evaluation Criteria in Solid Tumors. Results: We identified 53 radioresistant brain metastases (28\% RCC and 72\% melanoma) treated in 18 patients. The mean target volume and coverage was 6.2 +/- 9.5 mL and 95.5\% +/- 2.9\%, respectively. The mean prescription dose was 20 +/- 4.9 Gy. Forty lesions (75\%) demonstrated a complete/partial response and 13 lesions (24\%) with progressive/stable disease. Smaller target volume (p < 0.001), larger SRS dose (p < 0.001), and coverage (p = 0.008) were found to be positive predictors of complete response to SRS. Conclusion: SRS is an effective management option with up to 75\% response rate for radioresistant brain metastases. Tumor volume and radiation dose are predictors of response and can be used to guide the decision-making for patients with radioresistant brain metastases.
Keywords: Radiosurgery; Radioresistant; Renal cell carcinoma; Melanoma; Brain